2015
DOI: 10.1111/apt.13366
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota transplant for recurrentClostridium difficileinfection using long-term frozen stool is effective: clinical efficacy and bacterial viability data

Abstract: SUMMARY BackgroundFaecal microbial transplant (FMT) for recurrent Clostridium difficile infection (rCDI) is greatly facilitated by frozen stool banks. However, the effect of frozen storage of stool for greater than 2 months on the viability of stool bacteria is unknown and the efficacy of FMT is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 33 publications
5
107
0
6
Order By: Relevance
“…However, there have been no comparative trials investigating storage durations. As already described, a reduction in the viability of certain gut microbiota taxa was noted when faecal aliquots were frozen in 10% glycerol for 6 months74 and, as such, the working group agreed that 6 months was the acceptable limit for freezing of an FMT in glycerol. Storage at −80°C is recommended rather than −20°C to minimise sample degradation.…”
Section: Rationale For Recommendationssupporting
confidence: 56%
See 1 more Smart Citation
“…However, there have been no comparative trials investigating storage durations. As already described, a reduction in the viability of certain gut microbiota taxa was noted when faecal aliquots were frozen in 10% glycerol for 6 months74 and, as such, the working group agreed that 6 months was the acceptable limit for freezing of an FMT in glycerol. Storage at −80°C is recommended rather than −20°C to minimise sample degradation.…”
Section: Rationale For Recommendationssupporting
confidence: 56%
“…Colonoscopic delivery of donor FMT into the ileum or caecum was associated with a 91% cure rate for recurrent CDI 14. Observational studies highlighted similar success, describing cure rates of 88% (n=14/16)74 and 91%46 (n=21/23) in response to infusion of donor FMT into the caecum or terminal ileum. A further advantage of using colonoscopy to administer FMT has been to allow assessment for the presence of pseudomembranes; in certain reviewed studies, the presence or absence of pseudomembranes has influenced the FMT regimen used 18 73.…”
Section: Rationale For Recommendationsmentioning
confidence: 87%
“…Under the universal donor model, providers are responsible only for performing the procedure itself. Stool preparations can be cryogenically preserved without decreasing their effectiveness 12 and stored in health care facilities across Canada to avoid treatment delays.…”
Section: Key Pointsmentioning
confidence: 99%
“…It was shown that preserved slurries with or without glycerol exhibited remission rates similar to fresh FMT. Furthermore, only minor viability drops in the tested cultivable anaerobes over 6 months of frozen storage were reported (van Nood et al ., 2013; Youngster et al ., 2014; Costello et al ., 2015; Satokari et al ., 2015). However, artificially produced microbiota may lack the protective effect of a matrix naturally present in stool.…”
Section: Introductionmentioning
confidence: 99%